Systemic sclerosis sine scleroderma: An unusual presentation in scleroderma renal crisis (1995)
Renal involvement in systemic sclerosis (SSc) has a negative influence on prognosis. Cases of SSc sine scleroderma have been reported in which organ failure occurred but was not accompanied by cutaneous damage, which in some instances did develop later. We describe a patient who, after 6 months of symmetric polyarthritis, developed rapid progressive renal failure without skin changes. A diagnosis of scleroderma renal crisis, confirmed histologically, was made. Anti-RNAP III antibodies were positive. The patient developed typical scleroderma skin changes after renal failure. Despite treatment, SSc advanced to fatal endstage renal disease.